2012
DOI: 10.1002/mus.22311
|View full text |Cite
|
Sign up to set email alerts
|

A possible link of oxaliplatin‐induced neuropathy with potassium channel deficit

Abstract: A combination of sodium channel blockers with drugs that obstruct the blockage of potassium channels or contribute to their opening could be effective in preventing oxaliplatin-induced "hyperexcitability."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 39 publications
4
15
0
Order By: Relevance
“…In vitro studies of various vertebrate nerves showed that dysfunction of voltage-gated potassium and/or sodium channels is involved in oxaliplatin-induced axonal hyperexcitability (7). Thus, the channels involved in the neuropathy secondary to oxaliplatin treatment had been ill defined until recent reports clearly implicated the voltage-gated potassium channels as targets of oxaliplatin, offering new insights into the pharmacological prevention of peripheral neuropathy (24)(25)(26)(27). Our mouse model not only confirms the electrophysiological changes in potassium channels, but to the best of our knowledge, also demonstrates for the first time the therapeutic effect of mangafodipir.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies of various vertebrate nerves showed that dysfunction of voltage-gated potassium and/or sodium channels is involved in oxaliplatin-induced axonal hyperexcitability (7). Thus, the channels involved in the neuropathy secondary to oxaliplatin treatment had been ill defined until recent reports clearly implicated the voltage-gated potassium channels as targets of oxaliplatin, offering new insights into the pharmacological prevention of peripheral neuropathy (24)(25)(26)(27). Our mouse model not only confirms the electrophysiological changes in potassium channels, but to the best of our knowledge, also demonstrates for the first time the therapeutic effect of mangafodipir.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, oxaliplatin treatment causes a global change in ion channel expression that leads to a higher membrane potential and, thus, more robust firing of TRP channels. Additionally, modeling experiments have suggested that the reduction in potassium current in internodal regions of myelinated axons could lead to the nerve fiber defects first observed by Adelsberger, et al with action potential trains, and thus a stronger central response following a small peripheral stimulus[78]. The acute and chronic ion changes, however, were not considered.…”
Section: Mechanisms Of Peripheral Neuropathymentioning
confidence: 99%
“…Interestingly, both of these studies also found increased expression of hyperpolarization-activated channels (HCNs) permeable to both K + and Na + , which are known to increase nociceptor excitability and spontaneous firing in other pain conditions [27]. A simulation study has shown that oxaliplatin-induced decreases in potassium channel function and increases in sodium channel function can account for the observed nociceptor hyperexcitability [28]. In support of these findings, use of a voltage-gated K + channel opener, retigabine, to encourage neuronal hyperpolarization has been found to be effective in a mouse model of cisplatin neuropathy [29].…”
Section: Neuronal Alterations Associated With Cipnmentioning
confidence: 99%